A mitochondria-targeting photothermogenic nanozyme for MRI-guided mild photothermal therapy. Issue 100 (30th November 2018) - Qiu, Kangqiang; Wang, Jinquan; Rees, Thomas W.; Ji, Liangnian; Zhang, Qianling; Chao, Hui
Abstract : A mitochondria-targeting photothermogenic nanozyme was used to increase localized temperature and accelerate the catalysis of H2 O2 to ˙OH under NIR light irradiation for mild photothermal therapy. Abstract : Iridium complexes were used as a mitochondria-targeting agent to modify the surface of a photothermogenic nanozyme Fe3 O4 nanoparticles (Ir@Fe3 O4 NPs ). Upon NIR irradiation, Ir@Fe3 O4 NPs increase the localized temperature to 42 °C which accelerates the catalysis of ˙OH production from H2 O2 resulting in excellent mild photothermal therapy.